The Archival Institutionalization and Latin Americanization: the Inter American Centre of Archive Development (Córdoba, 1974-1989) - Silvano G. A.; Mansilla, Alicia R. (Revista General de Información y Documentación, 2023)
In 1974 The National University of Cordoba was born sponsored by the Organization of the American States and the Inter-American Archival Training Centre (CIFA), in the same building where the School of Archival Science from the University was housed. It kept that name until 1978 and then it changed it into Inter-American Centre of Archive Development (CIDA) until the last cohort Scholarship recipients finished the course in 1988. In this paper, we study the emerging process of the Latin-American archival institutionalization, where professional teaching and training were the first and founding edges. Here we describe the Argentinian and Latin American archival reality that promoted the creation of the centre and we characterise, through quantitative variables, its student population, its teaching and learning process, the paperwork for scholarship application as well as its methodology and pedagogical strategies. Similarly, we are going to pay attention to the extracurricular activities such as the visits and lectures of well-known specialists of their time and, finally, we are interested in presenting some intellectual biographies of its graduates to see how they entered the world of archival work of their time and how they used the profesional training that they received.